Green tea extracts for the prevention of metachronous colorectal polyps among patients who underwent endoscopic removal of colorectal adenomas: A randomized clinical trial. Issue 2 (April 2018) - Shin, Cheol Min; Lee, Dong Ho; Seo, A Young; Lee, Hyun Joo; Kim, Seong Beom; Son, Woo-Chan; Kim, Young Kyung; Lee, Sang Jun; Park, Sung-Hee; Kim, Nayoung; Park, Young Soo; Yoon, Hyuk
Summary: Objectives: To determine the preventive effect of green tea extract (GTE) supplements on metachronous colorectal adenoma and cancer in the Korean population. Materials and methods: One hundred seventy-six subjects (88 per each group) who had undergone complete removal of colorectal adenomas by endoscopic polypectomy were enrolled. They were randomized into 2 groups: supplementation group (0.9 g GTE per day for 12 months) or control group without GTE supplementation. The 72-h recall method was used to collect data on food items consumed by participants at baseline and the 1-year follow-up during the past 48 h. Follow-up colonoscopy was conducted 12 months later in 143 patients (71 in control group and 72 in the GTE group). Results: Of the 143 patients completed in the study, the incidences of metachronous adenomas at the end-point colonoscopy were 42.3% (30 of 71) in control group and 23.6% (17 of 72) in GTE group (relative risk [RR], 0.56; 95% confidence interval [CI], 0.34–0.92). The number of relapsed adenoma was also decreased in the GTE group than in the control group (0.7 ± 1.1 vs. 0.3 ± 0.6, p  = 0.010). However, there were no significant differences between the 2 groups in terms of body mass index, dietary intakes, serum lipid profiles, fasting serum glucose, and serum C-reactive protein levels (all p  > 0.05). Conclusion: This study of GTE supplement suggests a favorable outcome for the chemoprevention of metachronous colorectal adenomas in Korean patients (ClinicalTrials.gov number, NCT02321969 ).